WHEN VERBS BECOME NOUNS: GRAMMATICAL MBTAPHOR IN STUDENTS' ACADEMIC TEXTS - Refnaldi Refnaldi (Universitas Negeri Padang, 2015)
The major challenge, according to Systemic Functional Linguistics (SFL), for students in writing courses is the frequent use of grammatical metaphor in acaciemic texts. Grammatical metaphor is the key element of academic discourse and a